Evaluation, diagnosis and recovery of hydraulic concrete flooring in stretches located in Natal/RN City and in the Metropolitan Region (Research, Society and Development, 2021)
The paving of roads plays an important role among infrastructure works essential for urban dynamics. Wear is inevitable and inherent in its use. Monitoring the various defects due to the use of roads is an essential task for maintaining its functionality and safety. In this regard, this article aims to evaluate, diagnose and propose recovery and maintenance techniques for the concrete pavement lanes in two urban avenues in the city of Natal/RN and its metropolitan area. Despite both avenues were contemplated with a recovery/restructuring approximately five years ago, they present several pathologies in the concrete slabs of the rigid pavement. The objective assessment methodology used in this study was proposed by the National Department of Transportation Infrastructure (DNIT) in the Rigid Pavement Recovery Manual, along with visual inspections. The avenues were classified as Good. On the contrary, field observations showed the lack of repairs and maintenance services at several points. The frequency of simpler defects can be considered high, even in the absence of more serious defects. This highlights the importance of rigorous design practices, as well as the construction, the constant maintenance of the road, which are frequently neglected.